Ответы и объяснения

2014-04-14T13:19:26+04:00
а)4.37+6.7х=7.75+9.3х
6.7х-9.3х=7.75-4.37
-2.6x=3.38
x=3.38/(-2.6)
x=-1,3

б)4(3-х)-11=7(2х+5)
12-4x-11=14x+35
-4x-14x=35-12+11
-18x=34
x=34/(-18)
x=- \frac{18}{34}

в)\frac{1}{4}- \frac{1}{3}m = \frac{4,1}{4} - 3m
- \frac{1}{3}m+3m= \frac{4,1}{4}- \frac{1}{4}
- \frac{1}{3}m+ \frac{9}{3}m=4 \frac{1}{10} :  \frac{4}{1} -  \frac{1}{4}
 \frac{8}{3} m= \frac{41}{10} * \frac{1}{4} - \frac{1}{4}
 \frac{8}{3} m =  \frac{41}{40} -  \frac{1}{4}
 \frac{8}{3}m= \frac{41}{40} - \frac{10}{40}
 \frac{8}{3} m= \frac{31}{40}
m= \frac{31}{40} :  \frac{8}{3} =  \frac{31}{40} *  \frac{3}{8} = \frac{93}{320}